Working Americans, 1880-2010. Volume XI, Inventors & entrepreneurs - Derks, Scott (Amenia, NY : Grey House Pub., 2010)
A look at what kind of work Americans did, the homes they lived in, the goods they bought, the entertainment they sought, and the society and history that shaped their world ...
1880-1899 Introduction -- Developments in oil -- Buck Blanchard, traveling book salesman -- 1885 innovations -- Jan Matzeliger, revolutionized the shoe making industry -- 1886 innovations -- James "Jake" Ritty, invented the cash register -- 1900-1909 Introduction -- Marguerite Globman, attempted to invent streetcar fender -- An antitoxin for laziness -- Milton S. Hershey, created Hershey's chocolate -- Chocolate timeline -- Henry Wood, improved sales through mail-order seed catalog -- 1910-1919 Introduction -- James Murray Spangler, invented upright vacuum cleaner -- Vacuum cleaner timeline -- Domestic labor-saving invention timeline -- Harnessing heredity -- Grace Wiedersein, created the Campbell's kids -- Commercial canning timeline -- Food and food brand timeline -- Madam C.J. Walker, founded successful hair care business -- 1920-1920 Introduction -- Using the vacuum tube to hear -- Allan Kusse, harvested, shaped and distributed ice -- Refrigeration timeline -- Gideon Sundback, revolutionized the zipper -- Joseph Ridgeway, stock pool manager on Wall Street -- 1930-1939 Introduction -- George Mecherle, established State Farm automobile insurance -- Off the record: snuff -- Donald Davis, created innovative Wheaties ad campaign -- Radio timeline -- General Mills timeline -- Herbert Thomas Kalmus, invented technicolor -- Photographic film timeline -- 1940-1949 Introduction -- William J. Woods, made electric light affordable -- Electric light bulb timeline -- Lt. (Dr.) Mary Sears, overcame prejudices in the U.S. Navy -- Something new and strange in plastics -- Percy Lebraon Spencer, invented the microwave -- 1950-1959 Introduction -- Edwin Howard Armstrong, father of FM radio -- New York City in 1954 -- Large electronic machines -- Jack Simplot, created a fortune from french fries -- Jack Kilby, revolutionized the electronics industry -- Notable inventions of the 1950s -- 1960-1969 Introduction -- Coca-cola broadens its coverage -- Norton Simon, created multimillion dollar Hunt's empire -- Dr. Harry Coover, helped discover super glue -- Notable inventions of the 1960s -- Benjamin Eisenstadt, inventor of Sweet-n-low -- 1970-1979 Introduction -- Roy and Dotty Eargle, created successful antique business -- Bette Nesmith Graham, invented liquid paper -- History of office equipment -- First color telecast -- Hank Selman, pioneered computer leasing -- Notable inventions of the 1970s -- 1980-1989 Introduction -- Stephen Hassenfeld, fine tuned Hasbro's GI Joe -- Notable American toy timeline -- James Kennedy Jarrett, super accurate rifle guru -- Savannah River nuclear facility timeline -- Kidcorder: sold as a toy -- Bill Reindollar, created cash register repair service -- Business machines timeline -- 1990-1999 Introduction -- Marie Moffett, visionary of hydrogen fuel cells -- Jerry D. Neal, vanguard in emerging cell phone market -- Cell phones and wireless communications timeline -- Maurice Jennings, launched the Biscuitville restaurant chain -- Fast food and chain restaurant timeline -- Toying with science -- 200-2010 Introduction -- Rey Banatao, created a greener surfboard -- William Thomas Davis, launched Thomas Creek Brewery as retiree -- Gorm Bressner, industrial designer with many patents -- 3-D printing spurs a manufacturing revolution.
"A universal reference book."
Includes bibliographical references and index.
Keywords: Working class -- United States -- History -- 19th century; Working class -- United States -- History -- 20th century; United States -- Social conditions -- 19th century; United States -- Social conditions -- 20th century; Businesspeople -- United States -- 19th century; Businesspeople -- United States -- 20th century; Inventors -- United States -- 19th century; Inventors -- United States -- 20th century